Talazoparib monotherapy in metastatic castration-resistant prostate cancer with DNA repair alterations (TALAPRO-1): an open-label, phase 2 trial. Issue 9 (September 2021) - de Bono, Johann S; Mehra, Niven; Scagliotti, Giorgio V; Castro, Elena; Dorff, Tanya; Stirling, Adam; Stenzl, Arnulf; Fleming, Mark T; Higano, Celestia S; Saad, Fred; Buttigliero, Consuelo; van Oort, Inge M; et al.
Summary: Background: Poly(ADP-ribose) polymerase (PARP) inhibitors have antitumour activity against metastatic castration-resistant prostate cancers with DNA damage response (DDR) alterations in genes involved directly or indirectly in homologous recombination repair (HRR). In this study, we assessed the PARP inhibitor talazoparib in metastatic castration-resistant prostate cancers with DDR-HRR alterations. Methods: In this open-label, phase 2 trial (TALAPRO-1), participants were recruited from 43 hospitals, cancer centres, and medical centres in Australia, Austria, Belgium, Brazil, France, Germany, Hungary, Italy, the Netherlands, Poland, Spain, South Korea, the UK, and the USA. Patients were eligible if they were men aged 18 years or older with progressive, metastatic, castration-resistant prostate cancers of adenocarcinoma histology, measurable soft-tissue disease (per Response Evaluation Criteria in Solid Tumors version 1.1 [RECIST 1.1]), an Eastern Cooperative Oncology Group performance status of 0–2, DDR-HRR gene alterations reported to sensitise to PARP inhibitors (ie, ATM, ATR, BRCA1, BRCA2, CHEK2, FANCA, MLH1, MRE11A, NBN, PALB2, RAD51C ), had received one or two taxane-based chemotherapy regimens for metastatic disease, and progressed on enzalutamide or abiraterone, or both, for metastatic castration-resistant prostate cancers. Eligible patients were given oral talazoparib (1 mg per day; or 0·75 mg per day in patients with moderate renal impairment) until disease progression, unacceptable toxicity, investigator decision, withdrawal of consent, or death. The primary endpoint was confirmed objective response rate, defined as best overall soft-tissue response of complete or partial response per RECIST 1.1, by blinded independent central review. The primary endpoint was assessed in patients who received study drug, had measurable soft-tissue disease, and had a gene alteration in one of the predefined DDR-HRR genes. Safety was assessed in all patients who received at least one dose of the study drug. This study is registered with ClinicalTrials.gov, NCT03148795, and is ongoing. Findings: Between Oct 18, 2017, and March 20, 2020, 128 patients were enrolled, of whom 127 received at least one dose of talazoparib (safety population) and 104 had measurable soft-tissue disease (antitumour activity population). Data cutoff for this analysis was Sept 4, 2020. After a median follow-up of 16·4 months (IQR 11·1–22·1), the objective response rate was 29·8% (31 of 104 patients; 95% CI 21·2–39·6). The most common grade 3–4 treatment-emergent adverse events were anaemia (39 [31%] of 127 patients), thrombocytopenia (11 [9%]), and neutropenia (ten [8%]). Serious treatment-emergent adverse events were reported in 43 (34%) patients. There were no treatment-related deaths. Interpretation: Talazoparib showed durable antitumour activity in men with advanced metastatic castration-resistant prostate cancers with DDR-HRR gene alterations who had been heavily pretreated. The favourable benefit–risk profile supports the study of talazoparib in larger, randomised clinical trials, including in patients with non- BRCA alterations. Funding: Pfizer/Medivation.